Italy : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for Italy. The report finds that significant progress has been made in budget management, especially in recent years, and that Italy meets the standards of the code in many respects. In particular, roles of various branches of government are clearly defined, and in most state-owned or participated enterprises, noncommercial activities have been identified and reflected in the budget. Intergovernmental fiscal relations are evolving, following recent constitutional reform. Procurement practices meet European Union standards.